Exploring the relationships among creativity, engineering knowledge, and design team interaction on senior engineering design projects - Ibrahim, Badaruddin, author; De Miranda, Michael A., advisor; Gloeckner, Gene W., committee member; Siller, Thomas J., committee member; Makela, Carole J., committee member; Folkestad, James E., committee member (Colorado State University. Libraries, 2012)
In the 21st century, engineers are expected to be creative and work collaboratively in teams to solve or design new products. Research in the past has shown how creativity and good team communication, together with knowledge, can impact the outcomes in the organization. The purpose of this study was to explore the relationships among creativity, engineering knowledge, and team interaction on senior engineering design product outcomes. The study was conducted within the College of Engineering, Department of Mechanical Engineering, at Colorado State University. A purposeful sampling of 55 students who enrolled in Mechanical Engineering Design capstone course completed the instruments during this study, which included the Torrance Tests of Creative Thinking (TTCT) Figural Form A, and a pre and post Team Climate Inventory. Students were assigned to twelve design project teams at the beginning of the fall term, 2011, and the project outcomes were evaluated in the spring of 2012, during the senior design showcase. Eleven professional engineers and three graduate students were trained to evaluate the senior design outcomes. The students' engineering grade point average (GPA) was used as a proxy to represent engineering knowledge. Descriptive statistics were utilized to describe the sample in terms of their engineering GPA, creativity score, and team interaction score. Correlational analyses were executed to examine the relationships among the constructs of the study. At the design team level, results from this research indicate that there was no statistical significant relationship between the teams' creativity composite score and the design outcome. There was also no statistical significant relationship between the team interaction score and the design outcome. The team composite creativity score had no significant relationship with the team interaction score. The composite of team engineering knowledge had no significant relationship to the team interaction score. At the individual level, the correlation analysis indicated there was no statistically significant relationship between student engineering knowledge and the creativity score. Exploratory data analysis (EDA) was used to assess the interaction of the main constructs on the engineering design outcome. The EDA results indicate that only one team met the hypothesis that a team scored above average on engineering knowledge and creativity, and a positive team interaction climate would expect to score above average on their design outcome score. Two design teams scored above average on creativity and engineering knowledge, and positive team interaction climate yet scored below average on their design outcome, which went against the original hypothesis. One design team scored above average on their design outcome, but scored below average on the other three main constructs of the study. The remaining eight design teams did not show any consistent pattern of relationships among the three constructs and the design outcome score. This research adds to the body of work within creativity, engineering knowledge, and team interaction climate in engineering design, as well as engineering education. The findings suggest that creativity, engineering knowledge, and team interaction climate had little impact on the engineering design outcomes. The limitations and implications of the study and future research are also discussed.
Keywords: design solution; team interaction; product outcome; engineering design; engineering knowledge; creativity